Cerebral and muscle tissue oxygenation during exercise in healthy adults: A systematic review - Diego Orcioli-Silva; Victor Spiandor Beretta; Paulo Cezar Rocha Santos; Felipe Marroni Rasteiro; Anita Brum Marostegan; Rodrigo Vitório; Claudio Alexandre Gobatto; Fúlvia Barros Manchado-Gobatto (Elsevier, 2024)
Background: Near-infrared spectroscopy (NIRS) technology has allowed for the measurement of cerebral and skeletal muscle oxygenation simultaneously during exercise. Since this technology has been growing and is now successfully used in laboratory and sports settings, this systematic review aimed to synthesize the evidence and enhance an integrative understanding of blood flow adjustments and oxygen (O2) changes (i.e., the balance between O2 delivery and O2 consumption) within the cerebral and muscle systems during exercise. Methods: A systematic review was conducted using PubMed, Embase, Scopus, and Web of Science databases to search for relevant studies that simultaneously investigated cerebral and muscle hemodynamic changes using the near-infrared spectroscopy system during exercise. This review considered manuscripts written in English and available before February 9, 2023. Each step of screening involved evaluation by 2 independent authors, with disagreements resolved by a third author. The Joanna Briggs Institute Critical Appraisal Checklist was used to assess the methodological quality of the studies. Results: Twenty studies were included, of which 80% had good methodological quality, and involved 290 young or middle-aged adults. Different types of exercises were used to assess cerebral and muscle hemodynamic changes, such as cycling (n = 11), treadmill (n = 1), knee extension (n = 5), isometric contraction of biceps brachii (n = 3), and duet swim routines (n = 1). The cerebral hemodynamics analysis was focused on the frontal cortex (n = 20), while in the muscle, the analysis involved vastus lateralis (n = 18), gastrocnemius (n = 3), biceps brachii (n = 5), deltoid (n = 1), and intercostal muscle (n = 1). Overall, muscle deoxygenation increases during exercise, reaching a plateau in voluntary exhaustion, while in the brain, oxyhemoglobin concentration increases with exercise intensity, reaching a plateau or declining at the exhaustion point. Conclusion: Muscle and cerebral oxygenation respond differently to exercise, with muscle increasing O2 utilization and cerebral tissue increasing O2 delivery during exercise. However, at the exhaustion point, both muscle and cerebral oxygenation become compromised. This is characterized by a reduction in blood flow and a decrease in O2 extraction in the muscle, while in the brain, oxygenation reaches a plateau or decline, potentially resulting in motor failure during exercise.